Successful treatment with metronidazole and paromomycin for fulminant amoebic colitis during cytotoxic chemotherapy in a patient with small-cell lung cancer. (2021) - Kitaoka, Aya; Tanimura, Kazuya; Yasuda, Yuto; Nishioka, Kensuke; Hirayama, Yutaka; Uemasu, Kiyoshi; Iwashima, Daisuke; Arita, Sou; Kitai, Toshiyuki; Hoshi, Susumu; Date, Emi; Iizuka, Norishige; et al.
Abstract: We report the case of a 64-year-old man with advanced small-cell lung cancer who developed fulminant amoebic colitis during cytotoxic chemotherapy. During the first cycle of carboplatin/etoposide treatment, febrile neutropenia and grade 4 neutropenia developed. Because diarrhea, abdominal pain, and bloody stool were observed, abdominal computed tomography was performed, showing intussusception, and extensive colectomy and colostomy were performed. Histopathology of the colon revealed gastrointestinal necrosis and perforation due to Entamoeba histolytica infection. Amoebiasis improved after treatment with metronidazole and paromomycin. The second cycle of carboplatin/etoposide with dose reduction was completed, resulting in a partial response to small-cell lung cancer. The results of this case suggest that paromomycin is an additional option for amoebiasis during cytotoxic chemotherapy, and persistent diarrhea during cytotoxic chemotherapy should alert clinicians to consider the development of amoebiasis.